Structural Characterization and Anti-inflammatory Activity of a Galactorhamnan Polysaccharide From Citrus medica L. var. sarcodactylis - Luo, Bi; Lv, Jia; Li, Kejie; Liao, Peiran; Chen, Peng (Frontiers in Nutrition, 2022)
This study aimed to extract polysaccharides from Citrus medica L. var. sarcodactylis (finger citron fruits), analyze the structures and potential bioactivities. A new polysaccharides named K-CMLP were isolated and purified by DEAE-Sepharose Fast Flow and DEAE-52 cellulose column chromatography with the average molecular weight of 3.76×103 kDa. Monosaccharide composition analysis revealed that K-CLMP was consisted of rhamnose, galactose and glucose, with a molar ratio of 6.75:5.87:1.00. Co-resolved by methylation and two-dimensional NMR, K-CLMP was 1, 2-Rha and 1, 4-Gal alternately connected as backbone, and a small amount of glucose residues were connected to O-4 of rhamnose. The results of DPPH· and ABTS+· radical scavenging assays indicated that both crude polysaccharide CMLP and K-CLMP exhibited strong free-radical-scavenging properties in a dose-dependent manner. In addition, K-CMLP significantly inhibited the production of pro-inflammatory cytokine (IL-6 and TNF-α) and reactive oxygen species (ROS) in RAW264.7 cells treated with LPS. These results provide a basis for further use as one of the potential function food or natural medicine.